Functional and genetic study of M. tuberculosis glutamine synthetase (GS) and other factors possibly involved in GS metabolism - Hayward, Don (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2007.